Assessing analytic and intuitive reasoning using the cognitive reflection test in young patients with schizophrenia. (February 2020) - Puveendrakumaran, Pugaliya; Fervaha, Gagan; Caravaggio, Fernando; Remington, Gary
Highlights: Patients with schizophrenia may use less analytical reasoning when problem solving. We tested this hypothesis using the cognitive reflection test (CRT). Patients showed less analytical reasoning and more intuitive reasoning than controls. Patients without neurocognitive deficits also showed this cognitive bias. Patients with schizophrenia show reduced cognitive reflection compared to controls. Abstract: Cognitive biases may contribute to the formation and maintenance of positive symptoms in patients with schizophrenia. However, cognitive reflection (i.e., the ability to use analytical thinking to override intuitive responses) has not been explicitly examined in schizophrenia patients using the cognitive reflection test (CRT). Using the CRT, we examined the degree of analytical and intuitive reasoning employed during problem solving in patients with schizophrenia versus healthy controls. Fifty-eight outpatients with schizophrenia and fifty-eight age- and sex-matched healthy controls (18–35 years of age) participated in this study. In addition to CRT performance, neurocognition, apathy, impulsivity, depression, insight, and clinical symptoms were evaluated. Patients with schizophrenia produced significantly fewer analytical responses ( U  = 1167.00, p <0.05) and more intuitive responses ( U  = 1273.50, p <0.05) compared to healthy controls. Patients without significant cognitive impairment also produced fewer analytical responses compared to controls ( U  = 894.50, p <0.05). Among patients, analytical thinking was positively correlated with working memory ( r  = 0.27, p <0.05), and affective symptoms ( r  = 0.31, p <0.05). Analytical reasoning was not significantly correlated with positive symptoms, avolition, or impulsivity. Patients with schizophrenia demonstrate less analytical and more intuitive reasoning while problem solving compared to healthy controls. This reduction in cognitive reflection is not significantly explained by global cognitive impairment or motivational deficits.